(untitled) (Research, Society and Development, 2022)
Verruciform xanthoma is a relatively rare epithelial hyperplasia found in the oral mucosa, usually in the gingiva, alveolar mucosa and hard palate. However, it can also affect the skin and genital mucosa. This study aims to describe two cases of verruciform xanthoma and the importance of total excision of this lesion. The patients are two Caucasian females, 58 and 23 years old. On clinical examination, both had a somewhat verrucous lesion on the lateral border of the tongue. Surgical excision of the lesions was performed. The specimens were sent for anatomopathological examination, which showed epithelium with discrete parakeratosis, irregular acanthosis with epidermal crest elongation and an accumulation of numerous xanthomatous macrophages in the connective tissue, diagnosed as verruciform xanthoma. One of the patients had compromised surgical margins, in whom the lesion recurred. Although it is an uncommon lesion, verruciform xanthoma should be considered in the differential diagnosis of verrucous (benign and malignant) lesions of the oral cavity, and total excision prevents the recurrence of this lesion.